Ablation of uncoupling protein 3 affects interrelated factors leading to lipolysis and insulin resistance in visceral white adipose tissue. Issue 5 (22nd April 2022) - Gentile, Alessandra; Magnacca, Nunzia; de Matteis, Rita; Moreno, Maria; Cioffi, Federica; Giacco, Antonia; Lanni, Antonia; de Lange, Pieter; Senese, Rosalba; Goglia, Fernando; Silvestri, Elena; Lombardi, Assunta
Abstract: The physiological role played by uncoupling protein 3 (UCP3) in white adipose tissue (WAT) has not been elucidated so far. In the present study, we evaluated the impact of the absence of the whole body UCP3 on WAT physiology in terms of ability to store triglycerides, oxidative capacity, response to insulin, inflammation, and adipokine production. Wild type (WT) and UCP3 Knockout (KO) mice housed at thermoneutrality (30°C) have been used as the animal model. Visceral gonadic WAT (gWAT) from KO mice showed an impaired capacity to store triglycerides (TG) as indicated by its lowered weight, reduced adipocyte diameter, and higher glycerol release (index of lipolysis). The absence of UCP3 reduces the maximal oxidative capacity of gWAT, increases mitochondrial free radicals, and activates ER stress. These processes are associated with increased levels of monocyte chemoattractant protein‐1 and TNF‐α. The response of gWAT to in vivo insulin administration, revealed by (ser473)‐AKT phosphorylation, was blunted in KO mice, with a putative role played by eif2a, JNK, and inflammation. Variations in adipokine levels in the absence of UCP3 were observed, including reduced adiponectin levels both in gWAT and serum. As a whole, these data indicate an important role of UCP3 in regulating the metabolic functionality of gWAT, with its absence leading to metabolic derangement. The obtained results help to clarify some aspects of the association between metabolic disorders and low UCP3 levels.